A Case Report of a Pregnant Woman with COVID-19 and Tuberculosis. Issue 1 (2nd January 2023) - Song, Weiwei; Li, Jingru; Abulizi, Nadila; Peng, Tao; Fang, Ke; Xie, Na; Shu, Zhanjun
Abstract: We presented a case of a 32-week pregnant woman with coronavirus disease 2019 and tuberculosis delivering a healthy baby. She was treated with antituberculosis and other symptomatic treatments, and the nucleic acid test; the sputum tuberculosis bacterial smear turned negative; and the symptoms were significantly relieved.